37Cl/35Cl isotope ratio analysis in perchlorate by ion chromatography/multi collector -ICPMS: Analytical performance and implication for biodegradation studies. (October 2017) - Zakon, Yevgeni; Ronen, Zeev; Halicz, Ludwik; Gelman, Faina
Abstract: In the present study we propose a new analytical method for 37 Cl/ 35 Cl analysis in perchlorate by Ion Chromatography(IC) coupled to Multicollector Inductively Coupled Plasma Mass Spectrometry (MC-ICPMS). The accuracy of the analytical method was validated by analysis of international perchlorate standard materials USGS-37 and USGS -38; analytical precision better than ±0.4‰ was achieved. 37 Cl/ 35 Cl isotope ratio analysis in perchlorate during laboratory biodegradation experiment with microbial cultures enriched from the contaminated soil in Israel resulted in isotope enrichment factor ε 37 Cl = −13.3 ± 1‰, which falls in the range reported previously for perchlorate biodegradation by pure microbial cultures. The proposed analytical method may significantly simplify the procedure for isotope analysis of perchlorate which is currently applied in environmental studies. Highlights: Precise 37 Cl/ 35 Cl isotope ratio analysis in perchlorate by IC/MC-ICPMS is proposed. Satisfactory analytical performance of the proposed method was demonstrated. Tracing of perchlorate biodegradation in microcosm study resulted in ε 37 Cl = −13.3 ± 1‰.